Loud and proud: Passion and politics in the English Defence League - Pilkington, Hilary (New Ethnographies, 2016)
The book uses interviews, informal conversations and extended observation at EDL events to critically reflect on the gap between the movement's public image and activists' own understandings of it. It details how activists construct the EDL, and themselves, as 'not racist, not violent, just no longer silent' inter alia through the exclusion of Muslims as a possible object of racism on the grounds that they are a religiously not racially defined group. In contrast activists perceive themselves to be 'second-class citizens', disadvantaged and discriminated by a 'two-tier' justice system that privileges the rights of 'others'. This failure to recognise themselves as a privileged white majority explains why ostensibly intimidating EDL street demonstrations marked by racist chanting and nationalistic flag waving are understood by activists as standing 'loud and proud'; the only way of 'being heard' in a political system governed by a politics of silencing. Unlike most studies of 'far right' movements, this book focuses not on the EDL as an organisation - its origins, ideology, strategic repertoire and effectiveness - but on the individuals who constitute the movement. Its ethnographic approach challenges stereotypes and allows insight into the emotional as well as political dimension of activism. At the same time, the book recognises and discusses the complex political and ethical issues of conducting close-up social research with 'distasteful' groups.